Ability of metformin to deplete NAD+ contributes to cancer cell susceptibility to metformin cytotoxicity and is dependent on NAMPT expression - Zhuang, Yongxian; Haugrud, Allison B.; Schaefer, Meg A.; Messerli, Shanta M.; Miskimins, W. Keith (Frontiers in Oncology, 2023)
Background Nicotinamide adenine dinucleotide (NAD+) is vital for not only energy metabolism but also signaling pathways. A major source of NAD+ depletion is the activation of poly (ADP-ribose) polymerase (PARP) in response to DNA damage. We have previously demonstrated that metformin can cause both caspase-dependent cell death and PARP-dependent cell death in the MCF7 breast cancer cells but not in the MDA-MB-231 (231) breast cancer cells while in high-glucose media. We hypothesize that depletion of NAD+ in MCF7 cells via activation of PARP contributes to the cell death caused by metformin. Nicotinamide phosphoribosyltransferase (NAMPT), a key rate-limiting step in converting nicotinamide (vitamin B3) into NAD+, is essential for regenerating NAD+ for normal cellular processes. Evidence shows that overexpression of NAMPT is associated with tumorigenesis. We hypothesize that NAMPT expression may determine the extent to which cancer cells are sensitive to metformin. Results In this study, we found that metformin significantly decreases NAD+ levels over time, and that this could be delayed by PARP inhibitors. Pretreatment with NAD+ in MCF7 cells also prevents cell death and the enlargement of mitochondria and protects mitochondria from losing membrane potential caused by metformin. This leads to MCF7 cell resistance to metformin cytotoxicity in a manner similar to 231 cells. By studying the differences in NAD+ regulation in these two breast cancer cell lines, we demonstrate that NAMPT is expressed at higher levels in 231 cells than in MCF7 cells. When NAMPT is genetically repressed in 231 cells, they become much more sensitive to metformin-induced cell death. Conversely, overexpressing NAMPT in HEK-293 (293) cells causes the cells to be more resistant to metformin’s growth inhibitory effects. The addition of a NAMPT activator also decreased the sensitivity of MCF7 cells to metformin, while the NAMPT activator, P7C3, protects against metformin-induced cytotoxicity. Conclusions Depletion of cellular NAD+ is a key aspect of sensitivity of cancer cells to the cytotoxic effects of metformin. NAMPT plays a key role in maintaining sufficient levels of NAD+, and cells that express elevated levels of NAMPT are resistant to killing by metformin.